WHY DO BANKS ESTABLISH RISK MANAGEMENT COMMITTEES? - MOUN, PRETORIA (2015)
Abstract The aim of this study is to examine the rationale and impact of Risk Management Committee (RMC) on companies. Using a sample of 639 observations from 71 European banks between 2006 and 2014, this study employed a matched sample methodology to compare banks with a RMC and those without. Data was obtained from the BANKSCOPE database, Thomson Reuters financial DataStream and company websites. The results, based on our logistic regression analysis, suggests that commercial banks, banks domiciled in the United Kingdom and bigger banks in terms of total assets have a higher likelihood of establishing RMC holding all other variables constant. However, risk exposure (beta/vol), financial stability (z-score) and reputation (credit rating) variables are insignificant as signalling evidence of regulatory influence. Furthermore, the panel regression matching samples of banks with such a committee and those without reveal that banks with RMC did not perform significantly better than those without. Additionally, we found that the existence of RMC does not have any significant impact on share-holders equity and risk exposure. Overall, this study suggests that European banks may establish RMC to fulfil regulatory requirements, and therefore, there is a need for government to monitor their corporate governance and risk management activities since an independent and more effective risk committee is required to deal with risk.